CONCLUSION: Connections - Sarkar, Mahua (Visible Histories, Disappearing Women, 2008)
Much has been written in recent years about the relative absence of women as subjects in conventional, nationcentric histories, notwithstanding their frequent appearance in nationalist rhetoric as “potent symbols of identity and visions of society and the nation.”¹ While feminist critiques of the strategic incorporation of women, on the one hand, and elisions, on the other, constitute a generative context for this book, my main concerns here have been to explain why, through what discursive mechanisms, and within what contexts of large-scale social change, some women—in this case Muslim women in colonial Bengal—came to be more absent/neglected than